(untitled) (Journal of Universal Science Research, 2025)
Totemism is an ancient belief system that establishes a symbolic relationship between humans and natural entities, such as animals, plants, or celestial objects. These totems often serve as emblems of clans, tribes, or social groups, embodying spiritual, cultural, and linguistic significance. In linguoculture – a field that explores the intersection of language and culture – totemism plays a crucial role in shaping myths, rituals, taboos, and even linguistic expressions. This article examines totemism as a linguocultural phenomenon , analyzing its influence on Uzbek language, identity, and collective memory across different societies, whereas explores how totemic concepts survive in modern Uzbek linguoculture.